Training on making macromedia flash-based interactive learning media for teachers at Perintis 1 Bandar Lampung high school - Henry Kurniawan; Eko Subyantoro; Tri Sandhika Jaya (Future Science, 2018)
The Role of Human Resources is needed to adopt all the changes that occur. Human resources in schools must always be developed continuously to improve the ability to be in accordance with the demands of the educational environment. One way to improve teachers' skills and expertise is education and training. The training conducted at Bandar Lampung's Perintis 1 High School was aimed at teachers to improve their skills, knowledge and attitudes in order to improve current and future performance in developing students' processes, resources, and maturity in learning media by using computer software in the form of macromedia flash.This dedication resulted inan increase in teachers' knowledge and skills in making interactive learning media for macromedia flash programs, as seen from 29 teachers (67%) who did not introduce PBK software to all teachers (100%) knew the PBK (Computer Assisted Learning) software. Then from 8 teachers (0.186%) who already knew and used the macromedia flash program, all teachers knew and used this program. This can be seen in the initial demonstration that only 10 teachers were able to run the program. While progress and understanding with the use of macromedia flash, only 2 teachers who are able to run and understand macromedia flash make all teachers able to run and understand this program. The level of desire to make and use the macromedia program also increased by 8 teachers (18.6%) to 40 people (93%). Through this training activity, products were obtained in the form of macromedia flash learning CDs that can be used to achieve learning goals and create an interesting learning atmosphere.